Studi Komparasi Kinerja Konselor dalam Layanan Konseling Individual Berdasarkan Self Evaluation dan Peer Evaluation - Barida, Muya; Sutarno, Sutarno (Jurnal Kajian Bimbingan dan Konseling, 2018)
The purpose of this study was to evaluate school counselor performance in organizing individual counseling services using self evaluation and peer evaluation. This study uses descriptive survey approach through descriptive comparative study. Subjects are school counselors in Special Region of Yogyakarta, especially Bantul District. Data analysis used Mann-Whitney U test. Based on result obtained by Mann-Whitney U significance value between self evaluation with peer evaluation is 0,657 (> 0,05). This means that there is no significant difference in counselor performance evaluation based on self evaluation and peer evaluation instruments.